OPPORTUNITIES AND CHALLENGES FOR TEMPLE TOURISM IN THE KAMRUP DISTRICT OF ASSAM, INDIA - Das, Jayanta Kr. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Tourism has been a significant economic activity since ancient times. Nowadays, it has become a vital tool for the economic development of a country. Temple tourism is a specific type of tourism that involves traveling to temples primarily for religious purposes, cultural exploration and spiritual experiences. India is a land known for its rich cultural heritage. It has a large number of temples that serve as places of worship and attract millions of tourists and travelers. The State of Assam, situated in the north-eastern corner of the country, has numerous temples and monuments, which stand witness to the great historical and cultural past dating back to the medieval periods. Many ancient Hindu temples of Assam are rooted in mythological legends. The Kamrup district of Assam is home to several temples and shrines. The architectural styles, spiritual environment, fairs and festivals associated with them always attract the visitors. Every year, many pilgrims and tourists, both domestic and foreign, visit the place to offer prayer to the deities. Additionally, some come for research purposes. These temples offer significant potential for the development of local tourism. However, they face various challenges. This paper aims to outline the opportunities and challenges associated with the temples in the Kamrup district from a tourism perspective. Additionally, it proposes several recommendations to address these challenges.